Traction force generation in Plasmodium sporozoites is modulated by a surface adhesin - Ripp, Johanna; Probst, Dimitri; Singer, Mirko; Schwarz, Ulrich S.; Frischknecht, Friedrich (Journal of microscopy, 2025)
Plasmodium sporozoites are the highly polarised and motile forms of the malaria parasite transmitted by mosquitoes to the vertebrate hosts. Sporozoites use myosin motors to generate retrograde flow of actin filaments. These are linked to plasma membrane spanning adhesins, which in turn bind to the extracellular environment, resulting in forward directed gliding motility. The gliding motility machine of sporozoites leads to high speeds in the range of micrometres per second, which are essential for efficient migration in the skin. Yet, it is not clear how the individual parts of the machinery work together to generate force during migration. Sporozoites are elongated and curved cells and move on circular tracks in vitro. Sporozoites lacking the adhesin thrombospondin-related anonymous protein (TRAP) like protein, TLP, can still migrate in the skin, but at a lower level. TLP lacking sporozoites generate a lower force on the dorsal (nonsubstrate facing) surface as measured by laser tweezers. Here we use traction force microscopy to investigate motile sporozoites and the forces they produce during migration on their ventral surface. Both wild type and tlp(-) sporozoites show distinct foci of force generation, but tlp(-) sporozoites generating overall lower forces. Our findings demonstrate that TLP is an important element of the force-generating machinery during sporozoite gliding motility.
Gesehen am 26.11.2025